A Rarely Cause Of Urinary And Bloodstream Infections: Achromobacter Spp - Elif DEDE; Neslihan Mete Atasever; Mavera Uşaklıoğlu Erol; Behiye Benaygul Kacmaz; Öznur Bulut; Burçak Akar; AYPER SOMER; Bahar AKGÜN KARAPINAR; Betigul Ongen; Selda Hançerli Törün (Journal of Global Antimicrobial Resistance)
OBJECTIVES: Achromobacter spp. are aerobic, non-fermentative gram-negative bacteria. These are the causative pathogens of healthcare-associated infections in patients who are hospitalized for long periods, undergone invasive procedures, and are immunocompromised. We present seven confirmed cases of Achromobacter which is rarely a disease agent. METHODS: Clinical symptoms, laboratory test results and treatments of six cases of Achromobacter infections between January-2021 and June-2024 were analyzed retrospectively. RESULTS: Five of the patients (71.4%) were female and two were male. All patients had comorbidities [renal disease (n=2), and one patient each: cardiac disease, metabolic disease, neuroblastoma, liver transplant and factor 7 deficiency]. The hospital stay was >3 weeks in five (71.4%) patients. Four patients (57%) had central venous catheters(CVCs).Five of the growths were in blood culture (Bactec FX; Becton Dickinson-USA) and two in urine culture. The isolates were identified with the VITEK 2 Compact system and MALDI-TOF MS(bioMérieux-France). Achromobacter denitrificans growth was detected in three cases (two were from blood, one from urine) and Achromobacter xylosoxidas growth in the others.A meropenem-resistant strain was detected in the culture of a 7-year-old girl only with a diagnosis of recurrent neuroblastoma in septic shock. This patient was treated with colistin. Six of the strains obtained from other patients were susceptible to meropenem, five to piperacillin-tazobactam and trimethoprim-sulfamethoxazole. These patients were treated with meropenem and their CVC was removed. No mortality was observed. CONCLUSION: Although Achromobacter is a rare cause of hospital-acquired infection, it should be kept in mind in patients with prolonged hospital stays and those undergoing invasive procedures.